2001
DOI: 10.1128/aac.45.12.3293-3303.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Dicyclic and Tricyclic Diaminopyrimidine Derivatives as Potent Inhibitors of Cryptosporidium parvum Dihydrofolate Reductase: Structure-Activity and Structure-Selectivity Correlations

Abstract: A structurally diverse library of 93 lipophilic di-and tricyclic diaminopyrimidine derivatives was tested for the ability to inhibit recombinant dihydrofolate reductase (DHFR) cloned from human and bovine isolates of Cryptosporidium parvum (J. R. Vásquez et al., Mol. Biochem. Parasitol. 79:153-165, 1996). In parallel, the library was also tested against human DHFR and, for comparison, the enzyme from Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 76 publications
1
29
0
1
Order By: Relevance
“…In vitro kinetic studies also suggested that M. tuberculosis DHFR might have a lower affinity to trimethoprim compared with the homologous enzymes in other bacteria. The IC 50 of M. tuberculosis DHFR inhibited by trimethoprim is approximately 100-fold higher than E. coli DHFR, and its k i is 20-fold higher than that of the M. smegmatis enzyme [74,78,83,84]. …”
Section: Antifolatesmentioning
confidence: 99%
“…In vitro kinetic studies also suggested that M. tuberculosis DHFR might have a lower affinity to trimethoprim compared with the homologous enzymes in other bacteria. The IC 50 of M. tuberculosis DHFR inhibited by trimethoprim is approximately 100-fold higher than E. coli DHFR, and its k i is 20-fold higher than that of the M. smegmatis enzyme [74,78,83,84]. …”
Section: Antifolatesmentioning
confidence: 99%
“…(9) As can be seen, at the completion of the orientation step, the layout coordinates of molecules with different root fragments are approximately comparable, and the 2D coordinates now encode significant information about shared structural features.…”
Section: Methodsmentioning
confidence: 96%
“…With the exception of a recent study, 10 efforts to increase potency have often led to a decrease in species-specificity. 11,12 The idea that a novel allosteric site important for catalysis may be targeted for species-specific inhibitor design is an attractive prospect. In a previous validation study, we utilized virtual screening to target a pocket near the crossover helix and were able to find micromolar-range inhibitors of Cryptosporidium hominis thymidylate synthase–dihydrofolate reductase, Ch TS–DHFR.…”
Section: Introductionmentioning
confidence: 99%